Prediction of Exit Thickness and Its Compensation after Snake Rolling of Aluminum Alloy Thick Plate - Xiuliang Wang; Weidong Zhang; Yibo Ai (Advances in Materials Science and Engineering)
Asymmetrical deformation zone of the snake rolling process results in complex metal flow and unknown edge of the deformation zone. In this study, three assumptions about the location of exit thickness appear and the exit thickness is calculated by those three assumptions. By comparing the exit thickness obtained by formulas and the finite element method, one formula with high accuracy is verified and the plastic deformation of the thick plate under several snake rolling conditions is obtained. The results show that through comparing the minimum thickness in different assumptions, the exit of the plastic deformation zone is located at the midpoint of the line between two work rolls’ axis and the exit thickness is approximately equal to the length of the line which includes that midpoint and locates between the two work rolls in the vertical direction. Then with the increasing offset distance, the exit thickness increases and that leads to less deformation inside the plate. For maintaining the exit thickness equal to the preset value, an exit thickness compensation model is established according to the geometry of the deformation zone and verified by the results of simulations.